Legal Certainty of the Forced Share (Legitime Portie) of Legitimaries in Relation to Testamentary Grants that Violate the Forced Share - Andri Jatnika Sungkawa Putra; Felisitas Sri Marniati; M. Slamet Turhamun (Eastasouth Institute, 2026)
Inheritance arises upon a person’s death and is governed by civil inheritance law. Although Article 874 of the Indonesian Civil Code allows inheritance distribution through a will, such freedom is limited by the compulsory portion (legitime portie) protected under Article 913. In practice, testamentary grants that infringe upon the compulsory portion frequently occur, resulting in disputes among heirs, challenges to testamentary deeds, and inconsistencies in judicial decisions. This study examines the legal consequences of testamentary grants that violate the compulsory portion and analyzes the legal certainty afforded to legitime heirs. The research applies Soeroso’s theory of legal consequences to assess changes in legal relationships resulting from the annulment of testamentary grants and Jan Michiel Otto’s theory of legal certainty to evaluate the consistency of legal norms and judicial reasoning. Using a normative juridical method, the study relies on primary, secondary, and tertiary legal materials through statutory, case, conceptual, and analytical approaches. The findings reveal that testamentary grants violating the compulsory portion may be partially or wholly annulled, depending on the extent of the infringement. Such annulment serves as a legal sanction for violating mandatory inheritance provisions and affects the legal position of beneficiaries by reducing or eliminating rights obtained under the will. Legal certainty is reflected in the recognition of legitime heirs’ protected rights and the consistent application of inheritance norms by courts. The study recommends greater diligence by notaries in drafting wills and the development of jurisprudential guidelines to promote consistency in court decisions concerning legitime portie and inheritance disputes.